Psychometric evaluation of the Thai version of the Early Childhood Oral Health Impact Scale (Th-ECOHIS): a cross sectional validation study - Pattarawadee Leelataweewud; Varangkanar Jirarattanasopha; Chantana Ungchusak; Warangkana Vejvithee (BMC, 2021)
Abstract Background Early childhood caries (ECC) is prevalent in Thailand, but no appropriate tool has been available to measure its impact on children's quality of life. This study translated the Early Childhood Oral Health Impact Scale (ECOHIS), a widely used proxy-reported questionnaire developed in the United States for measuring the oral health-related quality of life of preschool children and their families, into Thai (Th-ECOHIS). The scale's psychometric properties were investigated in Thai caregivers and their children. Methods Cultural adaptation for the scale development within the Thai context was processed using forward-backward translation by experts. A face and content validation was conducted among 20 Thai caregivers to attain the final Th-ECOHIS. Psychometric testing was done on 3-year-old child-caregiver pairs in Bangkok using the interviewer-administered mode. Children's oral health was determined by caries experience (decayed, missing and filled primary teeth, dmft) and treatment need. The caregivers answered the Th-ECOHIS and global questions regarding their perception of the children's oral health. Across-items reliability was assessed by internal consistency using the Cronbach's alpha coefficient. Test-retest reliability was managed at a 2-week interval in 10% of the sample using the intraclass correlation coefficient calculated by two-way analysis of variance. The discriminant validity was tested by the relationship between the severity of dental caries, treatment need and Th-ECOHIS scores, using the Kruskal-Wallis test. Results A total of 214 child-caregiver pairs participated. Twenty-two percent had ECC (dmft 1-3) and 17.3% had severe ECC (dmft 4 or higher) with mean (SD) dmft 1.63 (2.92). All items in the original ECOHIS were retained in the Thai version. The test-retest reliability of Th-ECOHIS was 0.87; internal consistency was 0.85; the total Th-ECOHIS scores were significantly correlated with the global rating of oral health question (r = 0.604). Th-ECOHIS scores in both child and family impact sections and the total were significantly associated with the severity of caries (p <  0.001) and treatment need (p <  0.001). Conclusions Th-ECOHIS demonstrated good reliability and validity. It could be used on caregivers to assess the impacts of ECC on quality of life of Thai pre-school children and compared to other countries.